Santri's perception of sex education in the book of fathul izar: Analytical study at al-qodiriyah islamic boarding school windusari - Ananda Abro Wiant; Luluk Ifadah; Ana Sofiyatul Azizah; Husna Nashihin; Muhamad Okky Safi’i (At Turots: Jurnal Pendidikan Islam, 2023)
This study aims to examine students' perception of sexual education in the book Fathul Izar by K.H. Abdullah Fauzi at the Al-Qodiriyah Islamic Boarding School in Windusari. The background of this study is based on the still strong assumption that the discussion of sexuality is something taboo, even though Islam views sex as an integral part of religious teachings that need to be understood proportionately, ethically, and educationally. Islamic boarding schools, as institutions of religious education, play a strategic role in conveying this understanding accurately to students. This study uses a phenomenological approach to deeply understand the perception of students towards sex education in the book Fathul Izar. The type of research used is field research because it is carried out directly at the location where the subject is located. The method used is qualitative, with data collection techniques through observation, interviews, and documentation. The data source consists of primary data (students, administrators, and pondok village heads) and secondary data (Fathul Izar's book, journals, and pesantren documents).   Data analysis is carried out through the stages of data reduction, data presentation, and conclusion. The validity of the data is strengthened through triangulation of sources, techniques, and time. The results of the study show that students' perception of sex education in the book Fathul Izar is positive. They see the book as a guideline that teaches sexual education in a polite, in-depth, and based on Islamic values. Factors that affect the perception of students include family backgrounds, methods of delivery of ustaz, and the influence of the pesantren environment. The impact of sexual education based on the book of Fathul Izar can be seen in the mindset and association of students who are more ethical, responsible, and have spiritual readiness in entering domestic life. This research emphasizes the importance of learning sex education in pesantren through a classical book approach, not only to remove taboo stigma, but also as a preventive effort against sexual deviance and the formation of a character of students who are morally and spiritually intact.